2010
DOI: 10.1016/j.bbcan.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor receptor-2 in breast cancer

Abstract: Investigations over the last decade have established the essential role of growth factors and their receptors during angiogenesis and carcinogenesis. The vascular endothelial growth factor receptor (VEGFR) family in mammals contains three members, VEGFR-1 (Flt-1), VEGFR-2 (KDR/Flk-1) and VEGFR-3 (Flt-4), which are transmembrane tyrosine kinase receptors that regulate the formation of blood and lymphatic vessels. In the early 1990s, the above VEGFR were structurally characterized by cDNA cloning. Among these th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
164
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(172 citation statements)
references
References 205 publications
(235 reference statements)
4
164
0
4
Order By: Relevance
“…VEGFR-2, also known as kinase insert domain receptor (KDR), is a key receptor involved in malignant angiogenesis. Its activation promotes a number of other cellular changes that lead to tumor development and metastases [8,9]. KDR is highly expressed in breast cancer [10], suggesting that breast cancer is potentially treatable by reducing KDR expression.…”
Section: Introductionmentioning
confidence: 99%
“…VEGFR-2, also known as kinase insert domain receptor (KDR), is a key receptor involved in malignant angiogenesis. Its activation promotes a number of other cellular changes that lead to tumor development and metastases [8,9]. KDR is highly expressed in breast cancer [10], suggesting that breast cancer is potentially treatable by reducing KDR expression.…”
Section: Introductionmentioning
confidence: 99%
“…The VEGF receptor family contains 3 members, VEGFR-1 (Flt-1), VEGFR-2 (KDR/Flk-1) and VEGFR-3 (Flt-4), which are transmembrane tyrosine kinase receptors expressed on the surface of endothelial cells and are involved in the regulation and formation of blood and lymphatic vessels [2,3]. Among the VEGF receptors, VEGFR-2 is recognized to play a principal role in mediating VEGF-induced vessel formation [4]. Vascular endothelial growth factor receptor-2 is a marker for endothelial cell development and it directly regulates tumor angiogenesis, blocking VEGF and KDR/Flk-1 interaction by monoclonal neutralizing antibody targeting KDR/Flk-1 diminished tumor vascularity and inhibited tumor angiogenesis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Vascular endothelial growth factors and their receptors were reported to be expressed in various tumor cells [9][10][11][12][13][14]. In addition to acting on endothelial cells to modulate angiogenesis and lymphangiogenesis, the VEGF signaling is also directly activated in tumor cells to regulate cancer progression [4]. In the study of VEGFR expression in ovarian cancer, Klasa-Mazurkiewicz et al reported that the highest relative level of VEGFR-2 was detected in the early stage cancer, indicating the significance of neoangiogenesis in high VEGFR-2 expressed early stage ovarian cancer [15].…”
Section: Introductionmentioning
confidence: 99%
“…10 VEGFR2 is expressed by endothelial cells and various cancers including breast cancer and NSCLC. [11][12] As the principal receptor leading angiogenesis in tumoral tissue, VEGFR2 has potent tyrosine kinase activity and is primarily associated with the induction of angiogenesis mediated by VEGF. 13 VEGF-induced homodimerization of VEGFR2 leads to a strong autophosphorylation of VEGFR2 on tyrosine residues.…”
Section: Introductionmentioning
confidence: 99%